Government of Uttar Pradesh Planning Department Draft Annual Plan 1971-72 - Planning Commission (Planning Commission, 1970)
The major problems that are at present facing the State are in the field of utilisation of human resources, agriculture, irrigation and power resources, removal of regional imbalances, providing work to a large back-log of unemployed people in the labour force and those who are entering the labour force almost at a rate of one million per year, and, extending special help to small and marginal farmers whose capacity to bring about long and short term improvements in agricultural operations is very limited. With every advance which is made in the field of agriculture and slow but steady process of mechanisation, more and more people need to be diverted so nonagricultural occupations. The capacity of industrial sector and service trades to absorb this labour surplus is very limited. Therefore, the possibilities that are offered by the existing infra-structure are in the area of small industries which are based upon or linked with agriculture and are labour intensive in character. This is more true on account of the fact that the economy of the State is primarily based on agriculture and the rate of growth in secondary and tertiary sectors cannot be expected to absorb the increasing number of entrants to the labour market.
Draft Annual Plan 1971-72
Government of Uttar Pradesh